1994
DOI: 10.1111/j.1399-3054.1994.tb00427.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrate reductase in cotyledons of cucumber seedlings as affected by nitrate, phytochrome and calcium

Abstract: 1994. Nitrate reductase in cotyledons of cucumber seedlings as affected by nitrate, phytochrome and calcium. -Physiol. Plant. 91: 257-262.Regulation by the active form of phytochrome (PRJ) and the effect of Ca-* was examined with nitrate re.ducta.se (NR) in etiolated cucumber (Cucumis sativus cv. Beilpuig). Nitrate reductase activity (NRA) was studied in excised coty'iedons of cucumber seedlings grown io distilled water and in darkness for seven days at 24 ± 0.5°C. All experiments were performed in the dark an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…Therefore, the light-induced gene expression shown in Figure 5 is most likely dueto the response to light signals, not to the products of photosynthesis. This conclusion is consistent with previous observations in which light acts as a signal to induce the expression of NR genes in etiolated seedlings (Rajasekhar et al, 1988;Melzer et al, 1989;Becker et al, 1992;Bergareche et al, 1994). In addition to NR2, the mRNA levels of light-regulated nuclear-encoded photosynthetic genes CAB and RBCS were also reduced in cr88, further supporting the conclusion that cr88 is defective in the direct role that light plays in the regulation of NR2.…”
Section: Cr88 1s Defective In the Light Lnduction Of Nr2 And Photosynsupporting
confidence: 92%
See 3 more Smart Citations
“…Therefore, the light-induced gene expression shown in Figure 5 is most likely dueto the response to light signals, not to the products of photosynthesis. This conclusion is consistent with previous observations in which light acts as a signal to induce the expression of NR genes in etiolated seedlings (Rajasekhar et al, 1988;Melzer et al, 1989;Becker et al, 1992;Bergareche et al, 1994). In addition to NR2, the mRNA levels of light-regulated nuclear-encoded photosynthetic genes CAB and RBCS were also reduced in cr88, further supporting the conclusion that cr88 is defective in the direct role that light plays in the regulation of NR2.…”
Section: Cr88 1s Defective In the Light Lnduction Of Nr2 And Photosynsupporting
confidence: 92%
“…Light signals induce NR gene expression in etiolated seedlings (Rajasekhar et al, 1988;Melzer et al, 1989;Becker et al, 1992;Bergareche et al, 1994). The phenotypes of slow greening and underdeveloped chloroplasts suggest the possibility that cr88 is defective in light-regulated processes.…”
Section: Light Induction Of Genes Encoding Nr2 the Chlorophyll A/b Bmentioning
confidence: 99%
See 2 more Smart Citations
“…The red light spectrum induced a depression in the NR activity in needles, suggesting a lowered nitrate assimilation rate. In previous studies, it was identified that the spectra effects on NR activity depend on the length of vegetation [ 56 , 57 ] and that, when a significant effect occurred, it was the blue light spectrum that promoted NR activity through activation of the expression level [ 48 ]. Although the red light spectrum may exhibit night degradation of NR activity in Gracilaria tenuistipitata , it can also modify the circadian rhythm in the activity of NR, resulting in a decline in accumulation [ 58 ].…”
Section: Discussionmentioning
confidence: 99%